Innovative Demand Models for Telecommunications Services - McKemey, Kevin; Scott, Nigel; Afullo, Thomas; Kibombo, Richard; Sakyi-Dawson, O. (Innovative Demand Models for Telecommunications Services, 2023)
One of the key issues in promoting access for telephony and internet in Africa is the need for information about how new services are likely to be used by consumers - both citizens and small businesses. Regulators, telecoms operating companies and internet service providers (ISPs) all need to predict how quickly and extensively services are likely to develop if they are to establish viable access targets and network or service delivery schedules.
Keywords: Models; Telecommunications Services; Innovative